How sex and gender impact clinical practice : an evidence-based guide to patient care - Jenkins, Marjorie; Newman, Connie B. (Academic Press, an imprint of Elsevier, 2021)
How Sex and Gender Impact Clinical Practice: An Evidence-Based Guide to Patient Care enables primary care clinicians by providing a framework to understand differences and better care for patients in their practice. Each chapter covers a subspecialty in medicine and discusses the influence of sex hormones on disease, along with sex and gender-based differences in clinical presentation, physical examination, laboratory results, treatment regimens, comorbidities and prognosis. Illustrative case examples and practical practice points help each chapter come alive. A special chapter on communication differences between men and women assists clinicians in their conversations with patients. This book fills an important need by applying years of research findings to sex and gender specific medical care and demonstrating that an individualized approach to patient care will lead to improved detection, treatment and prevention of disease.